Methyl DNA phosphate adduct formation in lung tumor tissue and adjacent normal tissue of lung cancer patients. (12th March 2019) - Ma, Bin; Villalta, Peter W; Hochalter, J Bradley; Stepanov, Irina; Hecht, Stephen S
Abstract: The formation of methyl DNA adducts is a critical step in carcinogenesis initiated by the exposure to methylating carcinogens. Methyl DNA phosphate adducts, formed by methylation of the oxygen atoms of the DNA phosphate backbone, have been detected in animals treated with methylating carcinogens. However, detection of these adducts in human tissues has not been reported. We developed an ultrasensitive liquid chromatography–nanoelectrospray ionization–high resolution tandem mass spectrometry method for detecting methyl DNA phosphate adducts. Using 50 μg of human lung DNA, a limit of quantitation of two adducts/10 10 nucleobases was achieved. Twenty-two structurally unique methyl DNA phosphate adducts were detected in human lung DNA. The adduct levels were measured in both tumor and adjacent normal tissues from 30 patients with lung cancer, including 13 current smokers and 17 current non-smokers, as confirmed by measurements of urinary cotinine and 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol. Levels of total methyl DNA phosphate adducts in normal lung tissues were higher in smokers than non-smokers, with an average of 13 and 8 adducts/10 9 nucleobases, respectively. Methyl DNA phosphate adducts were also detected in lung tissues from untreated rats with steady-state levels of 5–7 adducts/10 9 nucleobases over a period of 70 weeks. This is the first study to report the detection of methyl DNA phosphate adducts in human lung tissues. The results provide new insights toward using these DNA adducts as potential biomarkers to study human exposure to environmental methylating carcinogens. Abstract : Using an ultrasensitive high-resolution tandem mass spectrometry method, methyl DNA phosphate adducts were detected for the first time in human lung tissues. These DNA adducts could serve as biomarkers to study human exposure to environmental and lifestyle methylating carcinogens.